Ромео и Джульетта - Шекспир Уильям (Зарубежная классика, 2011)
Экземпляры: ф.14 (20221219) / Инвентарный номер: 63038 / Цена: / Сис.шифр: 84(4Вел)-5 / Авт.знак: Ш 41 / ГРНТИ: 17.82.10 / ББК: 84(4Вел)-5